Influence of Ceramic Materials on Biomechanical Behavior of Implant Supported Fixed Prosthesis with Hybrid Abutment - Tribst, J. P.M. [UNESP]; Dal Piva, A. M.O. [UNESP]; Özcan, M.; Borges, A. L.S. [UNESP]; Bottino, M. A. [UNESP] (My University, 2019)
PURPOSE: This study evaluated the stress distribution in different cement-retained implant-supported prostheses with a hybrid abutment. MATERIALS AND METHODS: Two factors were evaluated: restorative material for the crown and hybrid abutment - zirconia, lithium disilicate and hybrid ceramic, yielding 9 combinations. For finite element analysis, a monolithic crown cemented on a hybrid abutment was modeled and cemented on a titanium base (Ti base). An oblique load (45°, 300 N) was applied to the fossa bottom and system fixation occurred on the bone's base. RESULTS: Each structure was evaluated separately to find the possible weaknesses in geometry and failure criteria. In this context, results demonstrated a significant decrease of maximum principal and von-Mises stresses concentration when crowns with high elastic modulus are cemented onto a hybrid abutment with lower elastic modulus. CONCLUSIONS: Considering this theoretical study for a Morse taper implant, the association of a rigid crown with a more resilient hybrid abutment reduces the tensile stress concentration in the restoration cervical region.
Keywords: Dental Ceramics; Dental Implant-Abutment Design; Dental Implants; Finite Element Analysis; Material Testing